A randomised, double blind, placebo controlled study of nebulised magnesium sulphate in asute asthma in children – The MAGNETIC study. (24th May 2012) - Powell, CVE
Abstract : Aim: To evaluate the role of nebulised magnesium as an adjunct to standard care in treating acute severe asthma. Methods: MAGNETIC was a double blind randomised placebo-controlled study in an acute paediatric setting. Children aged between 2 and 16 years with acute severe asthma (as defined by the BTS) were treated with standard care of a combination of three doses of nebulised salbutamol and ipratropium bromide and in addition were randomised to receive either nebulised magnesium or placebo every twenty minutes for the first hour. Primary outcome was the asthma severity score (ASS; score 0-9) at 60 minutes post treatment. Secondary outcomes were length of stay (LOS), need for intravenous bronchodilator treatment (IV), need for intensive care admission (PICU) or intubation, number of additional salbutamol administrations whilst in hospital and adverse events. Results: 508 children (median age 4.0 years; 58% males) were recruited from 30 centres. 252 children received nebulised magnesium and 256 children received placebo. There were no important clinical differences in baseline characteristics (table 1 ). Using ANCOVA regression those children with the shortest duration of attack showed the greatest response (difference in deviance=6.36 on 2 df, p=0.02 estimate −0.79 (−1.59, −0.03)) (table 2 ). Conclusion: Nebulised magnesium has a significant effect on the asthma severity score at one hour post initial treatment. This effect is most marked in those children who have the shortest duration of exacerbation at presentation.